A combined spectroscopic and molecular modeling Study on structure-function-dynamics under chemical modification: Alpha-chymotrypsin with formalin preservative - Biswas, Pritam; Adhikari, Aniruddha; Pal, Uttam; Mondal, Susmita; Mukherjee, Dipanjan; Ghosh, Ria; Obaid, Rami J.; Moussa, Ziad; Choudhury, Sudeshna Shyam; Ahmed, Saleh A.; Das, Ranjan; Pal, Samir Kumar (Frontiers in Chemistry, 2022)
Enzyme function can be altered via modification of its amino acid residues, side chains and large-scale domain modifications. Herein, we have addressed the role of residue modification in catalytic activity and molecular recognition of an enzyme alpha-chymotrypsin (CHT) in presence of a covalent cross-linker formalin. Enzyme assay reveals reduced catalytic activity upon increased formalin concentration. Polarization gated anisotropy studies of a fluorophore 8-anilino-1-napthelenesulfonic acid (ANS) in CHT show a dip rise pattern in presence of formalin which is consistent with the generation of multiple ANS binding sites in the enzyme owing to modifications of its local amino acid residues. Molecular docking study on amino acid residue modifications in CHT also indicate towards the formation of multiple ANS binding site. The docking model also predicted no change in binding behavior for the substrate Ala-Ala-Phe-7-amido-4-methylcoumarin (AMC) at the active site upon formalin induced amino acid cross-linking.